The Design and Implementation of the XWCETT Routing Algorithm in Cognitive Radio Based Wireless Mesh Networks - Velempini, M.; Kola, L. M. (Wireless Communications and Mobile Computing, 2018)
The Wireless Mesh Networks (WMNs) technology has recently emerged as a promising high-speed broadband communication. In a multi hop ad hoc cognitive radio network(CRN)environment, the performance of the network is degraded by the routing protocols, which are adapted from the traditional wireless networks. In an endeavor to optimize the performance of the CRNs, existing routing protocols can be adapted and optimized. Secondly, new dynamic routing protocols can be designed to meet the requirements of CRNs. This paper investigates the existing routing protocols in WMNs and proposes a new routing protocol called extended Weighted Cumulative Expected Transmission Time(xWCETT). .The xWCETT routing protocol was evaluated through network simulations using the NS2.Its performance was evaluated with respect to the end-to-end average latency, and the normalized routing load. The comparative evaluation results show that the xWCETT achieves superior results in terms of average throughput, latency, and the normalized routing load.
Article published in the Hindawi Wireless Communications and Mobile Computing Volume 2018
Keywords: Design; Implementation; XWCETT Routing Algorithm; Cognitive Radio Based Wireless Mesh Networks; Cognitive radio networks